2006
DOI: 10.1111/j.1467-9221.2006.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Strong Group Identities Fuel Intolerance? Evidence From the South African Case

Abstract: One conventional explanation of intergroup conflict is Social Identity Theory. That theory asserts that strong ingroup sympathies can give rise to outgroup antipathies which in turn fuel intolerance and conflict. While embraced by both macro-and microlevel analysts, this theory actually has not been widely investigated outside a laboratory environment. In this article, I test hypotheses linking group identities with intolerance, based on a 2001 survey in South Africa, a country where group identities have long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 43 publications
3
53
0
Order By: Relevance
“…On the contrary, recent research found that Malaysia is in fact, has been affected by subcultural pluralism (Robert, 1970) that is the differences of religion, race, and language of its three major ethnic group, and it is indeed, contributes to strong group identities (Gibson, 2006) and social polarization (Ramlee et al, 1999;Amir and Faridah, 2004;Balasubramaniam, 2006;Mohd, 2015) which impede ethnic political tolerance attitude, and thus affected ethnic political tolerance behaviour.…”
Section: International Journal Of Asian Social Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, recent research found that Malaysia is in fact, has been affected by subcultural pluralism (Robert, 1970) that is the differences of religion, race, and language of its three major ethnic group, and it is indeed, contributes to strong group identities (Gibson, 2006) and social polarization (Ramlee et al, 1999;Amir and Faridah, 2004;Balasubramaniam, 2006;Mohd, 2015) which impede ethnic political tolerance attitude, and thus affected ethnic political tolerance behaviour.…”
Section: International Journal Of Asian Social Sciencementioning
confidence: 99%
“…Tolerance also has been demarcated as a preparedness to give up unlikable thoughts or groups (Gibson, 2006) which also includes approving equal legal, social and political rights (Persell et al, 2001;Triandafyllidou and The Accept Pluralism Project, 2013). Contemporary scholars outline tolerance as diversity esteem, openness, inclusiveness of all ethnicities, races, and walks of life and cultivating oneself to respect others (Florida, 2003;Corneo and Olivier, 2009;Ramadan, 2010).…”
Section: International Journal Of Asian Social Sciencementioning
confidence: 99%
“…To overcome or avoid conflict, one needs to tolerate the very things one abhors, disagrees with, http://dx.doi.org/10.15405/epsbs.2018.02.34 Corresponding Author: S.M. Elissev Selection and peer-review under The study of problems of tolerance in democracy has the certain traditions (Vogt, 1997;Sullivan, Transue, 1999;Katnik, 2002;Gibson, 2006, Harell, 2010. In recent decades, there has been interest in the problem of formation of tolerance in the conditions of democratization of society (Peffley, Rohrschneider, 2003).…”
Section: Problem Statementmentioning
confidence: 99%
“…Dovidio, et al, 1998;Gaertner, et al, 1999;Brown 2000;Dovido & Kafati 1999;Gonzalez & Brown 2000;VanOudenhouven, et al, 1996. 39 Tutu 1996Gibson 2006. 40 Cairns 1994.…”
Section: External Threatmentioning
confidence: 99%
“…The Spirit in Luke-Acts subverts these identity-forming processes. 5 Grant 1993:43;Verkuyten 2005:122;Gibson 2006:697. 6 Tannehill 1996 'What the narrator presents first, when the reading is seeking basic orientation, will stand out and affect the reading of the rest of the story'.…”
Section: Zechariah and Elizabeth: Awakening Israelite Ethnic Identitymentioning
confidence: 99%